Supporting land use change assessment through Ecosystem Services and Wildlife Indexes. (June 2017) - Cervelli, Elena; Pindozzi, Stefania; Sacchi, Massimo; Capolupo, Alessandra; Cialdea, Donatella; Rigillo, Marina; Boccia, Lorenzo
Highlights: The analytical comparison of opportunities aimed at land remediation is provided. Three land use change scenarios are built through a multi-criteria evaluation. Scenarios are assessed through two different Ecosystem Services methods. Scenarios impacts on wildlife are evaluated, with deductive and indexes method. Approaches does not agree at all enhancing opportunity of methods integration. Abstract: Biodiversity and landscape management are recognized as crucial pillars of EU policies and strategies in order to ensure the integration of environmental issues with socio-economic needs at the base of human-made changes, in structural and functional terms. Midterm EU's Biodiversity Strategy (Feb 2th 2016) highlights the importance of biodiversity protection in Europe, not only in terms of ethical behavior but also due to its intrinsic value of the biodiversity loss, estimated in EUR 50 billion a year. The study is framed into the LIFE/ENV/IT/275 Ecoremed Project, aimed to development of eco-compatible remediation protocols for polluted soils in the area of Litorale Domitio Flegreo – Agro Aversano (declared Regional Interest Priority Site). The paper is aimed at defining potential land use change scenarios, by which positive biodiversity impacts could be provided. It entails 2 steps: definition of three LUC scenarios, through a multi-criteria approach; LUC scenarios assessment, through Ecosystem Services and through wildlife impact assessment. The study works on a physical-mathematical model, by which the multi-criteria evaluation for scenarios construction and the quantitative assessments have been integrated. The procedure allowed to identify the most LUC suitable areas and, then, the potential conflict areas between LUC scenarios and target species presence areas, with the specific identification of wildlife species more impacted, in order to calibrate mitigation interventions and strategies, through specific forms/interventions. Our evidence demonstrates an excellent land response to the LUC-LIFE protocols in terms of Ecosystem Services, while highlights the need to consider more targeted strategies with respect to wildlife impacts.